2020
DOI: 10.1371/journal.pone.0234893
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional combinatorial impact on the gut microbiota and plasma short-chain fatty acids levels in the prevention of mammary cancer in Her2/neu estrogen receptor-negative transgenic mice

Abstract: Breast cancer is the second leading cause of cancer-related mortality in women. Various nutritional compounds possess anti-carcinogenic properties which may be mediated through their effects on the gut microbiota and its production of short-chain fatty acids (SCFAs) for the prevention of breast cancer. We evaluated the impact of broccoli sprouts (BSp), green tea polyphenols (GTPs) and their combination on the gut microbiota and SCFAs metabolism from the microbiota in Her2/neu transgenic mice that spontaneously… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 88 publications
1
19
0
Order By: Relevance
“…Genistein has tumor inhibitory properties in vivo, although it's role in breast tissue is unstudied [38] . In animal studies, dietary modulation affects Adlercreutzia abundance in the stool where it may serve as a biomarker of the efficacy of anti-cancer dietary supplements [39] . Adlercreutzia abundance in the gut microbiome was positively correlated with BMI and inflammation as measured by serum leptin and adipsin concentrations in one study of obese patients [40] .…”
Section: Discussionmentioning
confidence: 99%
“…Genistein has tumor inhibitory properties in vivo, although it's role in breast tissue is unstudied [38] . In animal studies, dietary modulation affects Adlercreutzia abundance in the stool where it may serve as a biomarker of the efficacy of anti-cancer dietary supplements [39] . Adlercreutzia abundance in the gut microbiome was positively correlated with BMI and inflammation as measured by serum leptin and adipsin concentrations in one study of obese patients [40] .…”
Section: Discussionmentioning
confidence: 99%
“…Additional analyses from our study demonstrated that Allobaculum was negatively correlated with the levels of ALT, AST, TNF-α, and MDA suggesting that Allobaculum may be protective against inflammation and oxidative stress. The increase in relative abundance of Allobaculum in both treatment groups might explain the anti-inflammatory effect of probiotics, possibly through the action of short-chain fatty acids produced by Allobaculum [ 32 ]. Moreover, the increased abundance of Bifidobacterium , which has previously been shown to improve intestinal integrity [ 33 ], might explain the reduction of serum endotoxin and TLR-4 expression in probiotics-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al [ 51 ] investigated the protective effect of green tea polyphenols, broccoli sprouts, and both together in the development of mammary cancer. For that purpose, the researchers used Her2/neu transgenic spontaneous ER(-) mammary cancer mouse models.…”
Section: Influence Of Green Tea On Health Via Gut Microbiotamentioning
confidence: 99%